2015
DOI: 10.1007/s00217-015-2616-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of physicochemical, morphological and aromatic characteristics of Italian PDO dry-cured hams during processing

Abstract: The aim of this work was to follow the evolution of physico-chemical (dry matter, NaCl 12 concentration, pH, water activity), morphological (image analysis) and aromatic (e-nose) 13 characteristics of the three main Italian PDOs during processing, from slaughtering to end of 14 ripening. Main phenomena distinguishing the PDOs are NaCl concentration increase, which is 15 higher in Toscano than in Parma and San Daniele hams, starting from the salting phase. Water 16 activity values decrease during processing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
2
3
1
Order By: Relevance
“…Along the curing process, hams lose weight due to an increasing loss of water from 0 to 18 months of curing (6,16,23, 27% at 1, 3, 6, 12 month respectively, data not shown), with a plateau between 14 and 16 months (Table 2). Consequently, moisture showed a light tendency to decrease from 14-to 18-month hams, in line with what is generally observed in dry-cured ham [19][20][21]. Some modifications in protein content were also observed between seasoning classes, especially between 14-and 16-month hams and the 18-month group.…”
Section: Physical and Chemical Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…Along the curing process, hams lose weight due to an increasing loss of water from 0 to 18 months of curing (6,16,23, 27% at 1, 3, 6, 12 month respectively, data not shown), with a plateau between 14 and 16 months (Table 2). Consequently, moisture showed a light tendency to decrease from 14-to 18-month hams, in line with what is generally observed in dry-cured ham [19][20][21]. Some modifications in protein content were also observed between seasoning classes, especially between 14-and 16-month hams and the 18-month group.…”
Section: Physical and Chemical Analysissupporting
confidence: 86%
“…Instrumental color did not show any difference in the Semimembranosus muscles among the seasoning classes. Contrariwise, changes in color traits were observed in Celta ham, where Biceps femoris was less red and bright in the final seasoning phase [19], and in Teruel PDO drycured ham [23], and a progressive decrease of CIELAB parameters in lean ham was observed also by Giovannelli et al [21] for three Italian PDO dry-cured hams. In the latter study, as the curing process advances, Toscano ham was the one that showed the greater decrease in lightness during the last seasoning phases.…”
Section: Physical and Chemical Analysissupporting
confidence: 58%
“…The results may be due to the increased temperature and also due to the effects of salting and drying the legs several times. The moisture content at the aging period (35%) was lower than that one reported by Giovanelli et al [ 42 ], who found the moisture content decreased from 71.12% of the green pig hams and stabilized at 54.0% during the aging period. Zhao et al [ 43 ] and Zhang et al [ 44 ] also found a similar decrease trend of moisture content in Jinhua and Xuanwei hams.…”
Section: Resultscontrasting
confidence: 62%
“…Chemical and biochemical reactions between the breakdown products of nitrite and the breakdown products of fats and carbohydrates are very important in the development of typical aroma in cured meat products (Kaban, 2013). In dry-cured ham, many volatile compounds including different chemical groups such as alkanes, alkenes, aldehydes, ketones, alcohols, carboxylic acids, aromatic hydrocarbons, terpenes, esters, sulphur compounds, furans, pyrazines, amines and chloride compounds have been determined (Giovanelli, Buratti, Laureati, & Pagliarini, 2016;Martínez-Arellano, Flores, & Toldrá, 2016;Toldrá, 1998;Toldrá, Aristoy, & Flores, 2009). In pastırma, a short production time leads to a limited number of volatile compounds (Kaban, 2013).…”
Section: Practical Applicationsmentioning
confidence: 99%